The Advisory Opinion and the challenges that arise for religious education in Costa Rica - Castro Flores, Kattia Isabel (2019)
The Advisory Opinion of the Inter-American Court of Human Rights offers an interpretation of human sexuality, gender identity and the concept of family, which is the opposite of those promoted by religious education. This discrepancy contributes to the social confrontation that is experienced in Costa Rica around these topics. It is necessary the search for paths that promote a healthy coexistence amid the social diversity and beliefs that constitute the Costa Rican identity. Keywords: religious education, human sexuality, gender identity, family concept, social coexistence